The Arrangement of Investment Policy for the Protection of Indigenous People’s Rights - Wamafma, Filep; Moenta, Andi Pangerang; Patittingi, Farida; Ruslan, Achmad (Faculty of Law, Hasanuddin University, 2019)
The investment law policies have a positive influence on the interests and welfare of all Indonesian people. However, many legal problems arise due to overlapping regulations both at the central and regional government levels, and also in term of the implementation of decentralization. The results show that the arrangement of investment policy in West Papua against the recognition and respect for Papua indigenous people's rights are still limited to universal policies. Nationally, the policy has not clearly revealed how the form of recognition and respect for the rights of indigenous peoples and/or Papuan indigenous peoples rights related to the presence of investments in West Papua. On a regional scale, the provincial government policy in the form of regional regulations, only covers the scope of investment in West Papua, but does not fully explain how the form of recognition and respect for Papua indigenous peoples related to investment. Hence, related with the alignment of Papua indigenous people's rights in the field of ideal investment arrangements in West Papua was began with the concept of Bottom-up Development Planning, by involving indigenous peoples as a whole. This concept is based on the Optimum Suitable Yield (OSY) where the amount of natural resources that can be exploited must be based on calculations from various perspectives such as biology, economics, and even socio-political perspectives.